E4SE; Formula Of Business Success - Sorooshian, Shahryar (2017)
Small and Medium Enterprises (SMEs) are playing a major role in any country's economy, but many of SMEs are failing every day. SMEs have about 80% risk of failure! Our innovation is a tool, especially designed for SME characteristics. This innovation helps entrepreneurs, SMEs, SME advisors and auditors to predict, measure, and manage the SME performance based on strategic elements. Our innovation, E4SE formula, has ability to use both financial and non-financial factors. The E4SE is among very few available models in the SME context. It is granted by Malaysia ministry of higher education, and copyrighted by University Malaysia Pahang. It has been tested for validity, reliability, and application feasibility in two different countries. The product proved to be considerably useful to control and minimize the failure rate in SMEs and strengthen the country economy. E4SE’s potential market group includes business owners and SME supporting Institutes/organizations.